Assessing the factors influencing clients’ impulsive information seeking behaviour in using information resources and services of the academic library - Kaffashan Kakhki, Mojtaba; Harati, Hadi; Doreh, Yaser Aseman (Malaysian Journal of Library and Information Science, 2019)
The purpose of the present study was to identify and examine the factors that influence the library clients’ impulsive behaviour in using resources and services in an academic library. A survey research on the students population of Ferdowsi University of Mashhad in Iran was designed. A researcher developed questionnaire was used for data collection. After determining the validity and reliability of the research instrument, the questionnaire was distributed to 380 students based on a stratified random sampling procedure. Structural Equation Analysis, Path Analysis and the Linear Structural Relation (LISREL) software were used for data analysis. The results showed that (a) the time available to the students, and their interest in books and libraries, bring about surfing enjoyment and make the library a more enjoyable place for them; (b) individual features influence the students’ tendency towards impulsive use; (c) environmental features of the library directly affect students’ positive emotions and impulsive using behaviour, and indirectly affect it through their positive emotion; and (d) Surfing enjoyment had a direct effect on the students’ positive emotion and their tendency towards the impulsive use of the library resources and services. The direct relationship between the students’ positive emotion and their tendency towards impulsive use was not confirmed. However, the results of the path analysis showed a direct and significant effect of the positive emotion on the impulsive use of the library resources and services in the selected population.